Cases of Hashtagging as a Facilitator of the Protest Movements - A. V. Alekseev (Международная аналитика)
The article is devoted to the study of the protest movement on social networks. The novelty of the study is in its comparative analysis of protests in different regions of the world. Its relevance is determined by the need to identify the main trends of the protest movement that began a few years ago and continues to play a huge role in the life of society today – particularly during this period of integration and digitalization – which is confirmed by the statistics given in this article. Special attention is paid to autopoietic organizations: loyal to the regime, limitrophe and radical communities. We emphasize that activism in social networks is characterized by cyclicality and orientation towards international recognition. The work presents universal patterns of the formation of lexical units, expressed in the form of hashtags. It provides information on specific political techniques for using social media platforms in the United States, highlighting the most effective ways of constructing social media posts and using slogans and text that attract the attention of the audience. The paper also reveals the vital role of social networks in the political agenda of African countries such as Uganda, Kenya, etc. The paper highlights the protest movements that took place in Muslim countries during the Arab Spring and provides a brief description of the Hong Kong Umbrella Revolution. And it is the totality of lexical units, expressed in the form of hashtags, that fully reveal the nature of protest movements, providing an opportunity to analyse a specific protest not by one word, but by a set of lexemes to view a subject in various ways.